KEPAILITAN JOINT OPERATION DAN TANGGUNG JAWAB PARA PESERTA JOINT OPERATION - Zukhruffiyah Rizqi Addinda; Hadi Shubhan (Jurnal HUKUM BISNIS, 2018)
The Joint Venture bankruptcy which is a limited liability company has been regulated both in Law Number 40 of 2007 on Limited Liability Companies and Law Number 37 Year 2004 concerning Bankruptcy and Postponement of Obligation of Debt Payment. The form of a Joint Venture business entity has also been specified in several regulations. This is in contrast to the related Joint Operation rules which are a joint venture of two or more companies to run a project within a certain period of time and do not establish a new legal entity in accordance with Indonesian legislation. Lack of Joint Operation arrangements either in terms of definition, the form of the business entity or in the event of a bankruptcy petition against Joint Operation by a third party, it creates a legal void. Uncertainty in bankruptcy of Joint Operation is about the position of Joint Operation whether as the legal subject of bankruptcy and / PKPU, and result in responsibility for debt which is not paid by Joint Operation. Moreover, there have been cases of bankruptcy and PKPU against Joint Operation with Case Number 54 / PKPU / 2012 / PN. Jkt.Pst between PT. Putra Sejati Indomakmur to Joint Operating Body (JOB) Pertamina-Golden Spike Energy Indonesia Ltd.Keywords: bancrupty, business entity, Joint Operation